Electrospraying poly(lactic acid) microcapsules loaded with n-hexadecane for thermal energy storage systems. (December 2022) - Zhang, Shengchang; Liu, Pengqing; Chen, Yuan; Campagne, Christine; Salaün, Fabien
Abstract: Poly(lactic acid) (PLA) with good thermomechanical stability and biodegradability is selected as the shell for achieving the electro-microencapsulation of phase change materials. And, a series of n-hexadecane/PLA solutions with different compositions are electrosprayed into phase change microcapsules (mPCMs) in a green and high-efficiency way. The effects of PLA concentration and n-hexadecane addition in electrospraying solution on the microencapsulation process of n-hexadecane as well as the structures and properties of mPCMs are investigated. Experimental results indicate that spherical mPCMs with a mono-dispersed size distribution are obtained regardless of the variations in PLA concentrations and n-hexadecane additions. Encapsulated n-hexadecane tends to be randomly in the form of a poly-nuclear distribution. With increasing n-hexadecane addition, although both the mean diameter and the loading content of n-hexadecane in mPCMs increase gradually, the corresponding encapsulation efficiency of n-hexadecane decreases. And, higher loading content and higher encapsulation efficiency of n-hexadecane are obtained from higher PLA concentration solutions. When 5 wt% PLA/chloroform solution is used as matrix liquid to encapsulate n-hexadecane, the encapsulation efficiency of n-hexadecane in the mixture of 50 w/t% n-hexadecane and 50 wt% PLA can reach about 100%. Correspondingly, the phase-transition enthalpy also reaches 97 J/g. Meanwhile, because of the PLA matrix's protection, the phase-transition enthalpy of encapsulated n-hexadecane remains stable even after multiple heating-cooling processes. In addition, the cooperation of the PLA matrix with n-hexadecane chains also improves the mobility of PLA chains, resulting in a higher crystallization degree of the PLA matrix. This green, biodegradable, and durable n-hexadecane/PLA electrosprayed microcapsule can offer a new choice for the fields of thermal management and energy storage. Graphical Abstract: ga1